Cryogenic system for Polish Free Electron Laser Facility. Issue 1 (March 2020) - Banaszkiewicz, T; Chorowski, M; Duda, P; Poliński, J; Pietrowicz, S; Czuma, P; Krawczyk, P; Lorkiewicz, J; Nietubyć, R; Sekutowicz, J; Tazbir, J; Terka, M
Abstract: Polish Free Electron Laser facility (PolFEL) will be the first free electron laser in Poland. The PolFEL superconducting linear electron accelerator will first consist of an electron gun and four RI-HZDR type cryomodules, each housing two 9-cell superconducting TESLA RF cavities. Such configuration allows the generation of a continuous wave and long pulse beam with 5-50 MeV of energy and a long pulse electron beam with energy up to 187 MeV and photon wavelength ranged from THz region down to 55 nm. In the second stage an extension is planned with two cryomodules, which allows to reach 300 MeV electron beam energy and extreme ultraviolet (EUV) range of electromagnetic radiation. RF cavities will be operated at 2.0 K (optionally 1.8 K). For a four cryomodule linac the static and dynamic loads are estimated to be 61 W and 240 W @ 2 K, respectively. One of the investigated option is that the cooling power will be generated by the TCF50 Linde helium plant. The helium plant has a liquefaction capacity of 6 g/s and 120 W at 4.5K of cooling power. During the beam-on operation mode of the linac, a shortage of cooling power will be compensated by liquid helium supplied from an external dewar, while the warm helium gas stream exceeding the liquefaction capacity will be collected in pressurized storage tanks. During the beam-off mode, the helium gas will be recovered from the storage tanks and re-liquefied to the external dewar. The other option is the installation of a dedicated cryoplant fully corresponding to the linac cryogenic requirements.